The Role of Women's Leadership in Developing Organizational Culture (Case Study at the Family Planning Counseling Center, Medan Tembung District) - Nasution, Sopiah Widia Rahma; Ayu A., Delfriana; Aidha, Zuhrina (AMK : Abdi Masyarakat UIKA, 2024)
In an organization or institution, stereotypes that state the dominance of men as leaders are still very strong, but women's leadership has begun to emerge since the issue of human rights and gender equality was voiced loudly by feminist activists. In general, the potential that women have as religious, social, and cultural individuals is not much different from the leadership potential of men. The importance of understanding good and correct leadership models. This research aims to determine the role of women's leadership in developing organizational culture. This research method uses a descriptive qualitative approach and the data obtained in this research are the results of interviews, observations, and literature studies which are then analyzed descriptively qualitatively. It can be seen that women are also able to act as good leaders, no less good than men's leadership, while the leadership role of women in an agency or organization is also very large and has a positive impact. especially in developing culture in organizations, not only that, women's leadership can also think rationally and conditionally, and better understand environmental conditions and atmosphere, so the role of women's leadership in developing organizational culture is also as someone creative, innovative, and able to bring progress. Leadership in developing an organization or agency is not only a man, but a woman can also be a leader in developing a good and correct organization.